SHAPING THE FUTURE OF MEDICINE: THE SOCIAL IMPACT OF TECHNOLOGY IN MEDICAL EDUCATION AND PRACTICE - Umar Daraz; Farman Ali; Riaz Ahmad; Jahan‐Ul‐Mulk; Zakir Hussain (Policy Research Journal, 2025)
Background: Technological integration in medical education is reshaping healthcare delivery worldwide. Understanding its societal implications, particularly in regions like Peshawar, Khyber Pakhtunkhwa, Pakistan, is crucial. Despite existing literature, there's a need for comprehensive research focusing on local socio-cultural, economic, and regulatory factors. Method: A cross-sectional study was conducted in Peshawar, Pakistan, involving 400 participants from medical education and practice. Stratified random sampling ensured representation from educators, students, and practitioners. A structured questionnaire, based on the Likert scale and theoretical frameworks like TAM and DIT, was used for data collection. Ethical considerations were addressed, and reliability and validity were ensured through SPSS analysis. Results: Demographic analysis revealed a diverse sample, with trends indicating potential implications for technology adoption and proficiency. Chi-square tests demonstrated significant associations between technological integration and various aspects of human behavior in medical training and practice. Regression analysis confirmed a strong positive relationship between technological integration and human behavior. Conclusion: The study underscores the complex interplay between social factors, technological integration, and human behavior in medical training and practice. Findings emphasize the transformative potential of technology in advancing healthcare delivery and promoting equitable access to quality medical services. Efforts to bridge the digital divide and promote technological literacy are essential for sustainable integration.